CARPAL TUNNEL SYNDROME (DIAGNOSIS AND MANAGEMENT) - Devi Annisa; Sri Budhi Rianawati; Masruroh Rahayu; Neila Raisa; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2021)
Carpal Tunnel Syndrome (CTS) is a neuropathy disease that affects the median nerve with an incidence of around 90%. Carpal Tunnel Syndrome appears in 3.8% of the general population, with the highest prevalence occurring in women. There are several risk factors associated with CTS, namely medical and non-medical factors. The mechanism of carpal tunnel syndrome until now is still very complex and is not known with certainty, but compression and traction factors in the median nerve are thought to be the most common cause of CTS. Carpal Tunnel Syndrome can manifest clinically with subjective signs such as paresthesia, proprioceptive changes, and paresis, as well as objective signs, such as changes in motor sensitivity and function, positive Tinel and Phallen tests, and thenar muscle atrophy. The diagnosis of Carpal Tunnel Syndrome is based on the classic symptoms of pain, numbness, tingling, and/or burning sensation in the distribution of the median nerve in the hand, as well as the abnormal function of the median nerve based on nerve conduction studies. Conservative therapy is an option. Especially in Carpal Tunnel Syndrome patients with mild to moderate symptoms. Conservative therapy can be given in the form of corticosteroid and physical therapy. Patients with severe CTS or whose symptoms have not improved after four to six months of conservative therapy should be considered for surgical treatment.